Penilaian Sistem Informasi Akuntasi Siklus Penjualan Kamar di Hotel Garden Palace Surabaya - Widiar Onny Kurniawan; Kafidin Muzakki (Journal of Research and Technology, 2022)
Accounting information system is one of the instruments used by companies to achieve company goals. A good information system is an information system that is supported entryway an effective internal control. The company's internal controls must be periodically reviewed to be effective. The Garden Palace Hotel already has a computerized accounting information system, but internal control is not effectively linked to access control activities. Increase the effectiveness of inside control with five COSO components. The results of the research were: climate control, especially hierarchical construction, did not work as expected. This affects the adequacy of internal controls in the cycle of credit transactions. Doubled posting bets and error values ​​were still reasonable and the control measure that susceptible was access control.